2020
DOI: 10.1016/j.appdev.2020.101192
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the envelope: The who, what, when, and why of critical consciousness

Abstract: Deep-seated structural racism in the U.S. has been thrown into bold relief by the racially disproportionate impacts of COVID-19 and a series of highly visible police murders of Black Americans. Longstanding and intergenerational economic inequalities have been laid bare by the ensuing economic recession. This special issue's focus on how people critique, challenge, negotiate and change inequities is therefore particularly (and, unfortunately) relevant and timely. These three papers approach critical consciousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…For example, critical consciousness may be an internal resource to use in the vocational decision-making process when mentorship is limited (Bowers et al, 2020). However, despite domains of critical consciousness being theoretically and statistically distinct (Diemer, 2020;Diemer & Rapa, 2016;Diemer et al, 2017), PWT did not develop specific hypotheses about how components of critical consciousness act as moderators. This leaves the nuanced buffering effects of the critical consciousness subcomponents unclear and limits information to create interventions for those who face contextual barriers.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, critical consciousness may be an internal resource to use in the vocational decision-making process when mentorship is limited (Bowers et al, 2020). However, despite domains of critical consciousness being theoretically and statistically distinct (Diemer, 2020;Diemer & Rapa, 2016;Diemer et al, 2017), PWT did not develop specific hypotheses about how components of critical consciousness act as moderators. This leaves the nuanced buffering effects of the critical consciousness subcomponents unclear and limits information to create interventions for those who face contextual barriers.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…However, the complexity of critical consciousness has generated mixed results about the relations among subscales and vocational or well-being outcomes. Conceptually, the three dimensions of critical consciousness are separate and do not necessarily facilitate other dimensions (Diemer, 2020;Jemal, 2017). Supporting this claim, some research has found weak, nonsignificant, or negative correlations between these constructs (Diemer & Rapa, 2016;Diemer et al, 2017).…”
Section: Critical Consciousness In Vocational Psychologymentioning
confidence: 99%
“…This perspective may be especially salient for efforts to foster critical consciousness within the curriculum. The degree to which students with greater levels of privilege can develop critical consciousness remains a topic of discussion (Diemer, 2020). Our stance is that the integration of CCR and CC has potential benefit for all students, including those who profit, often unknowingly, from systems that marginalize their peers.…”
Section: Caveats and Challengesmentioning
confidence: 99%
“…Scholars of critical consciousness and critical youth studies have argued that research in these areas have focused heavily on the critical reflection and political efficacy dimensions of critical consciousness, at the expense of critical action (Diemer, 2020; Watts et al, 2015). YPAR projects provide an important avenue for investigating all the dimensions of critical consciousness, including how reflection and political efficacy may lead youth to take individual and collective action to improve or change their personal, interpersonal, and sociopolitical conditions (Foster-Fishman et al, 2010; Kornbluh et al, 2015; Scott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%